2016
DOI: 10.3390/s16020168
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RFID-Based Sensing Method for Low-Cost Bolt Loosening Monitoring

Abstract: In coal mines, bolt loosening in the cage guide is affected by the harsh environmental factors and cage hoist vibration, leading to significant threats to work safety. It is crucial, to this effect, to successfully detect the status of multipoint bolts of guide structures. This paper proposes a system to monitor bolt status in harsh environments established based on the RFID technique. A proof-of-concept model was demonstrated consisting of a bolt gearing system, passive UHF RFID tags, a reader, and monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The bolt loosening detection is essentially the detection and identification of the remaining amount of pretension force. In view of the different detection methods for the remaining amount of pretension force, the existing detection methods are divided into the detection method based on structural vibration signal (Guarino and Hamilton, 2014), the detection method based on the acoustic emission signal (Ding et al, 2014; Liang and Yuan, 2015; Ritdumrongkul et al, 2003; Yang and Chang, 2006), the detection method based on image recognition, and the detection method based on bolt angle and elongation (Cha et al, 2016; Park et al, 2015a, 2015b; Wu et al, 2016). The structural vibration signals mainly depend on the vibration characteristics of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The bolt loosening detection is essentially the detection and identification of the remaining amount of pretension force. In view of the different detection methods for the remaining amount of pretension force, the existing detection methods are divided into the detection method based on structural vibration signal (Guarino and Hamilton, 2014), the detection method based on the acoustic emission signal (Ding et al, 2014; Liang and Yuan, 2015; Ritdumrongkul et al, 2003; Yang and Chang, 2006), the detection method based on image recognition, and the detection method based on bolt angle and elongation (Cha et al, 2016; Park et al, 2015a, 2015b; Wu et al, 2016). The structural vibration signals mainly depend on the vibration characteristics of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…If the looseness process and consequently any spinning happens, the change is detected by a reader and displayed in interface software. Experiments have shown that the relationship between the reader and the tag for angles lower than 20 degrees yields best efficiency (Wu, et al, 2016).…”
Section: Radio Waves Processing Based Methodsmentioning
confidence: 99%
“…For what the latter is concerned, the detection of potential unsafe circumstances is surely important in vehicular as well as industrial environments, and it has already been investigated for applications in the context of structural health monitoring [17]. Cracks, corrosion, strains, bolt loosening, etc., are some possible structural circumstances where RFID tag sensors have been applied successfully [18], [19]. In this sense, screw relaxing is a situation which is rarely monitored (except for the manual inspection), even if it many times could be crucial for safety.…”
Section: Introductionmentioning
confidence: 99%